Iris Center Localization Based Hough Transform on Eye Image - Prahmana, I Gusti; Kristina Annatasia Br Sitepu; Adek Maulidya (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2026)
Localization iris center localization is stage crucial to the system biometrics eyes , tracking view (gaze tracking), as well analysis health based image . Research This propose method detection iris -based center Hough transform on image eye with channel work that emphasizes robustness to noise, variations lighting , and differences iris size . Stages used covering conversion image colored to grayscale for simplify information intensity , noise reduction using Gaussian Blur so that the iris edges are clearer stable , detection candidate iris circle using Hough Circle Transform with setting certain parameters , as well as , determining iris center based on coordinate circle best Hough voting results . Method performance evaluated in a way quantitative through error distance center (center localization error) to ground-truth and in general qualitative through visualization circle results detection on the image . Expected results show that Hough’s transformation is capable of give estimate consistent iris center in the image with condition moderate until complex , especially when the iris border is sufficient contrast to sclera . Research This contribute as relative approach​ simple , fast , and easy implemented For need localization iris center , at the same time provide base development advanced like adaptive iris segmentation and integration with method learning deep For increase resistance to conditions lighting extreme and occlusion by the eyelids or hair eye .